CSDM 2021
DOI: 10.25259/csdm_58_2021
|View full text |Cite
|
Sign up to set email alerts
|

Role of topical nadifloxacin as an empirical treatment in patients with skin and soft-tissue infections in India: A review and consensus

Abstract: Dermatologists often come across cases of skin and soft-tissue infections (SSTIs) which have diverse clinical presentations. Various local, systemic, and environmental risk factors predispose an individual to develop SSTIs. Topical antimicrobial agents are frequently used in superficial uncomplicated SSTIs, whereas systemic therapy is generally reserved for use in severe cases. However, emergence of resistance to these agents is becoming a common problem in clinical practice. This necessitates the use of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Healthcare practitioners may successfully treat bacterial infections while avoiding antimicrobial resistance with this medication. 3,4 Previous in vitro research on bacterial skin infections showed that Nadifloxacin is safe and effective against a range of bacteria. It's very effective against Streptococcus and Propionibacterium species.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare practitioners may successfully treat bacterial infections while avoiding antimicrobial resistance with this medication. 3,4 Previous in vitro research on bacterial skin infections showed that Nadifloxacin is safe and effective against a range of bacteria. It's very effective against Streptococcus and Propionibacterium species.…”
Section: Introductionmentioning
confidence: 99%